Scoping review on mental health and child protective services of migrated and refugee children and youth - Kraav Siiri-Liisi; Joubert Natalie; Anis Merja; Anand Janet; Malin Maili; Karukivi Max; Tolmunen Tommi (Psykiatrian Tutkimussäätiö, 2025)
One of the long-term consequences related to migration due to wars, violence, and ecological and climate crises, are the additional challenges to the health- and child welfare systems in the host country. Previous research has shown that the need for the help of migrant children and children of migrants differs from the help needs of the main population of the host country. In the current scoping review, our objective is to describe how the mental health and child protection services needs and use of child and youth refugees and migrants differ from those of the natives in the host country, and also to identify the main obstacles in receiving suitable mental health or child protective services. Implications for healthcare and child protective services are discussed.